Soluble and Solid Iron Reduction Assays with Desulfitobacterium hafniense - Lucrezia Comensoli; Julien Maillard; Wafa Kooli; Pilar Junier; Edith Joseph (Bio-Protocol, 2018)
There is a pressing need to develop sustainable and efficient methods to protect and stabilize iron objects. To develop a conservation-restoration method for corroded iron objects, this bio-protocol presents the steps to investigate reductive dissolution of ferric iron and biogenic production of stabilizing ferrous iron minerals in the strict anaerobe Desulfitobacterium hafniense (strains TCE1 and LBE). We investigated iron reduction using three different Fe(III) sources: Fe(III)-citrate (a soluble phase), akaganeite (solid iron phase), and corroded coupons. This protocol describes a method that combines spectrophotometric quantification of the complex Fe(II)-Ferrozine® with mineral characterization by scanning electron microscopy and Raman spectroscopy. These three methods allow assessing reductive dissolution of ferric iron and biogenic mineral production as a promising alternative for the development of an innovative sustainable method for the stabilization of corroded iron.